Direct and continuous dosing of propofol can saturate Ex vivo ECMO circuit to improve propofol recovery - Khurana Nitish; Sünner Till; Hubbard Oliver; Imburgia Carina E.; Yellepeddi Venkata; Ghandehari Hamidreza; Watt Kevin M. (The Journal of ExtraCorporeal Technology, 2023)
Background: Extracorporeal membrane oxygenation (ECMO) is a cardiopulmonary bypass device that provides life-saving complete respiratory and cardiac support in patients with cardiorespiratory failure. The majority of drugs prescribed to patients on ECMO lack a dosing strategy optimized for ECMO patients. Several studies demonstrated that dosing is different in this population because the ECMO circuit components can adsorb drugs and affect drug exposure substantially. Saturation of ECMO circuit components by drug disposition has been posited but has not been proven. In this study, we have attempted to determine if propofol adsorption is saturable in ex vivo ECMO circuits. Methods: We injected ex vivo ECMO circuits with propofol, a drug that is highly adsorbed to the ECMO circuit components. Propofol was injected as a bolus dose (50 μg/mL) and a continuous infusion dose (6 mg/h) to investigate the saturation of the ECMO circuit. Results: After the bolus dose, only 27% of propofol was recovered after 30 minutes which is as expected. However, >80% propofol was recovered after the infusion dose which persisted even when the infusion dose was discontinued. Conclusion: Our results suggest that if ECMO circuits are dosed directly with propofol, drug adsorption can be eliminated as a cause for altered drug exposure. Field of Research: Artificial Lung/ECMO